RFID Enabled Sensor System Design - Grout, Ian; Rodrigues da Silva, Alexandre Cesar [UNESP]; IEEE (Ieee, 2017)
In this paper, the design and operation of a sensor system design using radio frequency identification (RFID) and near field communication (NFC) principles is presented. Data and control signals between an external computer and the sensor electronics are provided for using an RFID card or tag and so this interface is both portable and contactless. The sensor electronics would be embedded within a physical object which would make the electronics inaccessible using a physical wired connection and hence wireless communications would be a design requirement. The paper presents the requirements for the interface, along with the design and development of a prototype electronic system.
Keywords: RFID; NFC; Sensor; Embedded